Tooth-Whitening with a Novel Phthalimido Peroxy Caproic Acid: Short Communication - Stübinger S; Altenried S; Ren Q (Dove Medical Press, 2024)
Stefan Stübinger,1 Stefanie Altenried,2 Qun Ren2 1Department of Oral and Cranio-Maxillofacial Surgery, Research Group MIOSTE University Hospital Basel, Basel, 4032, Switzerland; 2Laboratory for Biointerfaces, Empa - Swiss Federal Laboratories for Materials Science and Technology, St. Gallen, 9014, SwitzerlandCorrespondence: Stefan Stübinger, Department of Oral and Cranio-Maxillofacial Surgery, Research Group MIOSTE University Hospital Basel, Spitalstrasse 21, Basel, 4032, Switzerland, Tel +41 61 265 70 70, Email stefan.stuebinger@unibas.chAbstract: Professional tooth whitening in the dental office is a popular cosmetic procedure and is performed under carefully monitored conditions. This allows the controlled application of a relatively high concentration of bleaching ingredients based on hydrogen peroxide or peroxide derivatives which produce reactive oxygen species, and consequently induce enamel erosion, alteration of the microhardness of the teeth, irritation of the gums, pain or post bleach sensitivity. This short communication describes the successful and reliable application of a new professional tooth whitening technique using a novel phthalimido peroxycaproic acid complex while avoiding reactive oxygen species.Keywords: in-office bleaching, SEM, composite gel, hydrogen peroxide, esthetics